Analysis of the Production of Pronominal Constructions in Spanish in a Learner Corpus. (29th August 2019) - Fernández-Montraveta, Ana; Vázquez, Glòria
Abstract : It is a well-established fact that pronominal constructions are one of the most difficult areas for learners of Spanish as a second language (Tremblay, 2006, Toth, 2000). This study aims to contribute to the area of language learning and materials design by drawing a general picture of the production of pronominal constructions applying corpus linguistics methodology, following the recommendations of Zyzick (2006). The analysis has been carried out taking into consideration three aspects: the students' L1, the semantics of each construction, and the type of errors found. In order to conduct our study, a corpus of 2, 532 real pronominal sentences (written by learners of Spanish from levels B1 and C1) was compiled. Findings show that students with a Romance L1 do not perform better than students with a non-Romance L1. Also, the semantics of the different types of pronominal constructions seem to have an influence on the students' performance. Finally, errors of overgeneralization are more common than errors of omission. In addition, the latter decrease in higher levels whereas the former seem to increase. These results may be used to reconsider some aspects of the teaching of Spanish as a foreign language.